Non-parametric Camera-Based Calibration of Optical See-Through Glasses for AR Applications - Klemm, Martin; Seebacher, Fabian; Hoppe, Harald (2016 International Conference on Cyberworlds (CW), 2016)
This work describes a non-parametric camera-based method for the calibration of Optical See-Through Glasses (OSTG). Existing works model the optical system through perspective projection and parametric functions. In the border areas of the displays such models are often inadequate. Moreover, rigid calibration patterns, that produce only a small amount of non-equidistant point correspondences, are used. In order to overcome these disadvantages every single display pixel is calibrated individually. The error prone user interaction is avoided by using cameras placed behind the displays of the OSTG. The displays show a shifting pattern that is used to calculate the pixels' locations. A camera mounted rigidly on the OSTG is used to find the relations between the system components. The obtained results show better accuracies than in previous works and prove that a second calibration step for user adaptation is necessary for high accuracy applications.